2022
DOI: 10.3389/fimmu.2022.1029423
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic spectrum in recessive STING-associated vasculopathy with onset in infancy: Four novel cases and analysis of previously reported cases

Abstract: Gain-of-function variants in the stimulator of interferon response cGAMP interactor 1 (STING1) gene cause STING-Associated Vasculopathy with onset in Infancy (SAVI). Previously, only heterozygous and mostly de novo STING1 variants have been reported to cause SAVI. Interestingly, one variant that only leads to SAVI when homozygous, namely c.841C>T p.(Arg281Trp), has recently been described. However, there are no entries in public databases regarding an autosomal recessive pattern of inheritance. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…Nevertheless, a few studies suggested that some clinical features of SAVI may be related to corresponding mutations. Several authors confirmed that patients with the inherited p.V155M variant have a less severe disease course than those with de novo variants [ 1 , 16 ]. A systematic review demonstrated that, compared to patients with the p.V155M mutation, patients with p.N154S mutations had earlier disease onsets and more severe skin lesions, with no differences in respiratory symptoms [ 2 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, a few studies suggested that some clinical features of SAVI may be related to corresponding mutations. Several authors confirmed that patients with the inherited p.V155M variant have a less severe disease course than those with de novo variants [ 1 , 16 ]. A systematic review demonstrated that, compared to patients with the p.V155M mutation, patients with p.N154S mutations had earlier disease onsets and more severe skin lesions, with no differences in respiratory symptoms [ 2 ].…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports suggested that SAVI remains to be reported as an exclusively autosomal-dominant disease [ 6 ]. However, recent reports have presented that autosomal-recessive inheritance caused by homozygous missense pathogenic variants (such as p.R281W) was found in STING1 [ 16 ]. Thus far, the genotype-phenotype correlations are not definite due to the limited cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another puzzling feature that seems to be particularly frequent in genes associated with IEI is the observation that pathogenic variants of the same gene can follow different modes of inheritance. For example, both an autosomal recessive as well as an autosomal dominant inheritance is known to be causative in the genes such as MEFV ( 71 , 72 ), STING1 ( 73 , 74 ) and AICDA ( 75 , 76 ).…”
Section: Current Challengesmentioning
confidence: 99%
“…Studies have reported variant R284S/G and R281Q/W in exon 7 of STING causing SAVI, some patients also suffered from severe interstitial lung disease ( 82 84 ). Konno et al.…”
Section: Targeting Cgas-sting Signaling Alleviates Pulmonary Fibrosismentioning
confidence: 99%